Transformasi Budaya literasi di SDN 36 Kota Ternate: Dampak Program Kampus Mengajar Angakatan 4 - Marlina, Yetni (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
The Teaching Campus is one of the Independent Learning Campus (MBKM) programs which aims to help improve literacy, numeracy, technology adaptation and school administration. The presence of this campus teaching program provides opportunities for students throughout Indonesia to improve their soft skills and hard skills. The aim of this research is to determine the form of implementation of the teaching campus program, the obstacles faced and the impact of the teaching campus program on student literacy culture at SDN 36 Kota Tenate. This research uses a qualitative approach with a case study type of research. Data collection techniques use observation, interview and documentation techniques. Based on the data that has been taken, it shows that the implementation of the campus teaching program for class 4 at SDN 36 Tenate City is in the form of creating a School Literacy Movement (GLS) program, creating Reading Corner media, activating the library, pulling the lucky string, and a literacy map. The obstacles faced in implementing campus teaching programs include a lack of coordination between the central government and regions/schools as well as inadequate facilities and infrastructure. The impact of the implementation of the 4th generation campus teaching program on student literacy culture can be seen from the results of students' literacy ability tests using the MBKM portal which shows a change of 25.64% from 0-100%. So the programs implemented by teaching campus students can have an impact on students' literacy culture, even though it is small if measured from the specified range.